Inspired to Lend a Hand? Attempts to Elicit Prosocial Behavior Through Goal Contagion - Brohmer, Hilmar; Fauler, Andreas; Floto, Caroline; Athenstaedt, Ursula; Kedia, Gayannée; Eckerstorfer, Lisa V.; Corcoran, Katja (Frontiers in Psychology, 2019)
Helping often occurs in a broader social context. Every day, people observe others who require help, but also others who provide help. Research on goal contagion (Aarts, Gollwitzer & Hassin, 2004) suggests that observing other people’s goal-directed behavior (like helping) activates the same goal in the observer. Thus, merely observing a prosocial act could inspire people to act on the same goal. This effect should be even stronger, the more the observer’s disposition makes him or her value the goal. In the case of prosocial goals, we looked at the observer’s Social Value Orientation (SVO; Van Lange, 1999) as a moderator of the process. In three studies (N = 126, N = 162 and N = 371), we tested the hypothesis that prosocial observations (vs. control) will trigger more subsequent casual prosocial behavior the more the observer is prosocially oriented. In line with the original research, we used texts as stimulus material in Study 1 and short video clips in Study 2 and 3. In Study 1 and 2, SVO was measured directly before the manipulation was induced and in Study 3 even a week prior to the actual experiment. Additionally, we included a second control condition video clip in Study 3, which did not depict human beings. Despite thoroughly developed stimulus material and methods, we found no support for an effect of the interaction, nor of the prosocial observation, but some support for an effect of SVO on casual helping behavior in Study 1 and 2. A mini meta-analysis revealed an effect equivalent to zero for goal contagion and a small, but robust SVO effect across studies. The main implication for the theory of goal contagion is that prosocial goals might not be as contagious as other goals addressed in the literature. We suggest a meta-analytic review of the literature to identify suitable goals and moderators for the goal contagion process.